Mesozeaxanthin Protects Retina from Oxidative Stress in a Rat Model - Orhan, Cemal; Akdemir, Fatih; Tuzcu, Mehmet; Şahin, Nurhan; Yilmaz, Ismet; Deshpande, Jayant; Şahin, Kazım (Mary Ann Liebert, Inc, 2016)
Purpose: Mesozeaxanthin (MZ) is able to protect against chronic and cumulative eye damage and neutralize free radicals produced by oxidative stress. The objective of the present study was to evaluate the protective potential of MZ against retinal oxidative damage and growth and transcription factors of the retina in rats fed with high-fat diet (HFD). Methods: Twenty-eight Sprague Dawley rats were randomly divided into the following 4 groups: (1) Control, (2) MZ (100 mg/kg bw/d), (3) HFD (42% of calories as fat), and (4) HFD+MZ (100 mg/kg bw/d) group rats were administered daily as supplement for 12 weeks. Results: Consumption of HFD was associated with hyperglycemia and oxidative stress as reflected by increased serum MDA concentration (P < 0.001). No measurable zeaxanthin (Z)+MZ and lutein (L) could be detected in the serum of control and HFD rats, whereas they were observed in the serum of MZ-administered rats. Retinal antioxidant enzyme [superoxide dismutase (SOD) and catalase (CAT)] activities were significantly decreased in the HFD group compared to the normal group (P < 0.01). However, retinal antioxidant enzymes were restored close to normal levels in HFD+MZ-treated rats (P < 0.05). The retina of rats fed with HFD had increased levels of vascular endothelial growth factor (VEGF), inducible nitric oxide (iNOS), intercellular adhesion molecule-1 (ICAM-1), and nuclear factor-kappa B (NF-kappa B) levels and decreased nuclear factor erythroid 2-related factor 2 (Nrf2) and heme-oxygenase 1(HO-1) levels compared to the healthy rat retina (P < 0.001). Rats treated with MZ partially alleviated the inflammation as reflected by suppressed VEGF, iNOS, ICAM, and NF-kB levels and increased Nrf2 and HO-1 levels in the retina of rats fed (P < 0.05). Conclusions: Results from the present study suggest that MZ has protective effects on the retina and the ability to modulate oxidative stress of retina in rats fed an HFD by suppressing retinal lipid peroxidation and regulating growth and transcription factors.
Keywords: HFD; meso-zeaxanthin; retina